Intestinal helminth infection induces highly functional resident memory CD4+ T cells in mice. Issue 2 (28th November 2016) - Steinfelder, Svenja; Rausch, Sebastian; Michael, Dörte; Kühl, Anja A.; Hartmann, Susanne
Abstract : Preferential maintenance of Th2 memory cells in intestinal nematode infection. CD4+CD44+CD62L−T cells expressing GATA3+ persist primarily in nonlymphoid tissues after abrogation of infection and express specific markers. While Th2 memory cells from the lamina propria express CD69, those found in the peritoneal cavity express IL‐33R and display innate functions. Abstract : Immunity to intestinal nematodes requires CD4⁺ Th2‐cell responses, including IL‐4 and IL‐13 production. Chronic infection with intestinal nematodes leads to downregulation of these responses, and few functional T helper (Th) 2 cells are detected in secondary lymphoid organs in the chronic phase or after abrogation of infection. Here, we show with a natural murine infection with Heligmosomoides polygyrus that highly functional memory Th2 cells persist in the lamina propria and in addition in the peritoneal cavity (PC) after abrogation of infection. While both tissue‐resident memory (TRM ) populations proliferate in situ and express IL‐4, IL‐5, and IL‐13 upon TCR‐dependent stimulation, only peritoneal memory cells express high levels of the IL‐33 receptor and produce IL‐5 and IL‐13 upon TCR‐independent stimulation with IL‐33 and IL‐7. Most importantly, PC‐derived TRM cells are able to mediate anti‐helminthic effects by decreasing the fecundity of female worms upon transfer into recipient mice. These results show that nonlymphoid compartments can serve as reservoirs for Th2 memory cells, and furthermore that innate effector function of Th2 memory cells is restricted to CD4⁺ memory T cells residing in the PC.